Non-malarial febrile illness: a systematic review of published aetiological studies and case reports from Africa, 1980–2015 - Elven, J; Dahal, P; Ashley, EA; Thomas, NV; Shrestha, P; Stepniewska, K; Crump, JA; Newton, PN; Bell, D; Reyburn, H; Hopkins, H; Guérin, PJ; et al. (BioMed Central, 2020)
Background The availability of reliable point-of-care tests for malaria has heralded a paradigm shift in the management of febrile illnesses away from presumptive antimalarial therapy. In the absence of a definitive diagnosis, health care providers are more likely to prescribe empirical antimicrobials to those who test negative for malaria. To improve management and guide further test development, better understanding is needed of the true causative agents and their geographic variability.